KEWENANGAN PERADILAN TIPIKOR PASCA BERLAKUNYA UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - Mohammad Sahlan (Arena Hukum, 2016)
Abstract Â The purpose of this journal is to analyze the competency of the administrative court and the corruption court to examine and decide the element of abused of power in corruption act after enacment of the Government Administration Acts and the legal implication when the legislation policy provides the authority to examine and decide upon the matter to the two institutions court, and the arrangements to ideal concept in the future. This is a normative law research, using conceptual approach, statute approach and case approach. The result of this research shows that theoretically and practically the concept of